HOLISTIC APROACH IN TMJ CLINICAL EXAMINATION - Alina Apostu; Valeria Pendefunda; Oana Ţănculescu; Corina Cristescu; Adrian Doloca; Gabriela Ifteni (Romanian Society of Oral Rehabilitation, 2015)
The TMJ exam represents a main stage in clinical examination of each patient, especially in temporomandibular desorder. Usually the clinical examination in dentistry is concentrated in oral aria, TMJ is examed just when the patients acuse simptoms. In a few minutes we can diagnose completely and corectly all problems of oro-facial system following a standard protocol.